The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/cncr.25226
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome in localized extranodal mucosa‐associated lymphoid tissue lymphomas treated with radiotherapy

Abstract: BACKGROUND: This study was conducted to evaluate the long-term outcomes in patients with stage IE and IIE mucosa-associated lymphoid tissue (MALT) lymphomas treated with involved field radiotherapy (RT). METHODS: Between 1989 and 2004, 192 patients with stage I and II MALT lymphomas were treated. The report focuses on 167 patients who received RT. The median age of patients was 58 years with a female predominance (2:1). Presenting sites were as follows: orbital adnexa in 71 patients, salivary glands in 28 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(150 citation statements)
references
References 38 publications
(52 reference statements)
10
133
4
3
Order By: Relevance
“…However, Vrieling et al [26] reported that there were 7 recurrent cases among 56 patients with gastric MALT lymphoma who achieved CR after RT, and that 2 of them showed recurrence in the stomach. On the other hand, Goda et al [27] reported absence of disease recurrence in 25 patients with gastric MALT lymphoma who achieved CR after RT. In our study, one of the three recurrent cases showed transformation to diffuse large-cell lymphoma, but none of the above-mentioned recurrent cases with gastric MALT lymphoma transformed to diffuse large-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Vrieling et al [26] reported that there were 7 recurrent cases among 56 patients with gastric MALT lymphoma who achieved CR after RT, and that 2 of them showed recurrence in the stomach. On the other hand, Goda et al [27] reported absence of disease recurrence in 25 patients with gastric MALT lymphoma who achieved CR after RT. In our study, one of the three recurrent cases showed transformation to diffuse large-cell lymphoma, but none of the above-mentioned recurrent cases with gastric MALT lymphoma transformed to diffuse large-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, one of the three recurrent cases showed transformation to diffuse large-cell lymphoma, but none of the above-mentioned recurrent cases with gastric MALT lymphoma transformed to diffuse large-cell lymphoma. However, according to the reports of Tsai et al [21] and Goda et al [27], 22.5 and 33.3%, respectively, of the recurrent cases transformed to diffuse large-cell lymphoma among the patients with MALT lymphoma originating from organs other than the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goda et al [15] reported the long-term outcome of localized MALT lymphomas treated with radiotherapy: the CR rate was 99 %, the 10-year recurrence-free rate was 76 %, and the overall survival rate was 87 %. These findings suggest that radiotherapy is a good choice in the interest of organ preservation, while also producing the desired therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab, which is an anti-CD20 monoclonal antibody, is strongly suggested in a systemic disease (20). This case was an EBV-negative lymphoma and the disease extent was limited to the eye; therefore, we decided that a local radiotherapy would be the treatment modality because radiotherapy is one of the competent options among the treatment modalities for orbital MALT lymphoma (21)(22)(23)(24)(25). Recent studies reported that a radiotherapy dose range of 25∼35 Gy achieved ex-cellent survival rates for stage IEA orbital MALT lymphoma (26).…”
Section: Case Reportmentioning
confidence: 99%